Sustainability-Oriented Spiritual Leadership in Resilient Islamic Boarding Schools - Amin, Muhammad; Arifin, Samsul; Fathurrochman, Irwan; Khatipah, Khatipah; Elman, Moh. (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to develop a resilient management model by integrating sustainability practices and spiritual leadership in the context of Islamic boarding schools. Using a qualitative approach with a multi-site study design, this research was conducted at the Nurul Jadid Paiton Islamic Boarding School in East Java, which represents different institutional characteristics, namely traditional, semi-modern, and modern boarding schools. Data were obtained through in-depth interviews with clerics, teachers, administrative staff, and senior students, supplemented by participatory observation of educational and managerial activities, as well as the pesantren's institutional and curricular aspects. Data analysis used the interactive model of Miles and Huberman, which includes three main stages, namely data reduction, data presentation, and conclusion drawing/verification. To maintain the validity of the research results, layered source triangulation was applied to make the findings more valid and reliable. The findings identify three essential components that reinforce institutional resilience: (1) spiritual leadership based on Islamic principles such as sincerity (ikhlas), consistency (istiqamah), and trustworthiness (amanah); (2) sustainability-oriented practices including economic self-reliance, curriculum innovation, and digital adaptation; and (3) the integration of spiritual and sustainability dimensions into a holistic model of resilient management. The proposed model, termed Resilient Islamic Educational Management, contributes both theoretically and practically. Theoretically, it enriches Islamic education management discourse by bridging contemporary management theory with Islamic spiritual traditions. Practically, it equips Islamic boarding schools' leaders with an adaptive framework to strengthen governance, autonomy, and global competitiveness. Ultimately, this study emphasizes that the sustainability of Islamic boarding schools is deeply rooted not only in organizational and economic strategies but also in value-driven spiritual leadership.